Generation of the Anomalous Vortex Beam by Spiral Axicon Implemented on Spatial Light Modulator - Huang, Xiaoting; Chang, Zehong; Zhao, Yuanyuan; Wang, Yunlong; Zhu, Xindong; Zhang, Pei (Frontiers in Physics, 2022)
The anomalous vortex beam (AVB), whose paraxial local topological charge varies with propagation, has potential applications in quantum information, laser beam shaping, and other fields. However, there are currently no efficient optical devices to generate AVBs. In this paper, we propose an efficient pure-phase device called spiral axicons. We theoretically analyze the spiral axicon, and then experimentally verify its performance by implementing a spiral axicon on spatial light modulator. Our work provides an alternative method for generating AVB, which will facilitate its application in different fields.